Do Racial Descriptors Confuse Viewers? The Utility of Suspect Race for Identification in Crime Stoppers and Similar Broadcast Descriptions - Loggins, Ginger Miller (My University, 2010)
Local news programs across the country regularly broadcast descriptions of criminal suspects received from law enforcement agencies. For example: “Police describe the suspect as a White male in his mid-forties, about 230 pounds and 6 foot 2 inches tall. He had a moustache and goatee and wore a red t-shirt and jeans.” Do such descriptions really help viewers envision or recognize the correct suspect? This study compares the effectiveness of racially explicit descriptions, those that state a suspect's race, to racially implicit descriptions, those that describe a suspect's skin tone. Results indicate that viewers were more likely to correctly identify a tanned White man or a light-skinned Black man as the suspect when the description detailed the suspect's skin tone rather than stating his race. Racial descriptors generally led viewers to focus on race, sometimes ignoring other characteristics, such as age, also provided in the description. Such descriptors particularly encouraged biased identification of dark-skinned African Americans. Based upon these findings, the author urges broadcasters to avoid including race in any descriptions because it appears to confuse viewers.
Keywords: Broadcasting; Race; Criminal suspects; Blacks; Whites; African Americans